2022
DOI: 10.3389/fonc.2022.829708
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of External Beam Radiation Therapy Modalities for Hepatocellular Carcinoma With Macrovascular Invasion: A Meta-Analysis and Systematic Review

Abstract: PurposeWe performed a systematic review and meta-analysis to compare external beam radiation therapy modalities for hepatocellular carcinoma (HCC) with macrovascular invasion (MVI).MethodsStudies were selected from online databases from the date of inception to November 2021. The outcomes of interest were overall survival (OS), objective response rate (ORR), and local control rate (LCR).ResultsForty-four studies (n = 3730) were selected from 1050 articles. The pooled 1-year OS were 60.9%, 45.3%, and 44.9 for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, owing to the physical characteristics of photons, SBRT has limited tissue-sparing benefits, particularly for the surrounding normal tissues. SBRT also increases the irradiation dose to the normal liver tissue and the risk of radiation-induced liver disease, especially in large lesions [ 36 ]. Thus, SBRT is recommended only for small tumors (generally < 3–5 cm), because of the normal liver constraints.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the physical characteristics of photons, SBRT has limited tissue-sparing benefits, particularly for the surrounding normal tissues. SBRT also increases the irradiation dose to the normal liver tissue and the risk of radiation-induced liver disease, especially in large lesions [ 36 ]. Thus, SBRT is recommended only for small tumors (generally < 3–5 cm), because of the normal liver constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Although modern series of photon stereotactic ablative RT have shown excellent local control outcomes in the treatment of HCC [ 95 ], protons have dosimetric advantages, especially in certain clinical scenarios. There is a growing body of evidence supporting the use of proton therapy for HCC [ 26 , 46 , 47 , 55 , 57 , 58 , 67 ]. Multiple dosimetric studies have shown its advantage in sparing the nearby organs at risk, namely the normal liver parenchyma, and subsequently decreasing the risk of radiation-induced liver disease [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of proton therapy in the case of vascular thrombosis was also demonstrated in a prospective study [ 55 ] and while using a risk-adapted PBT regimen with simultaneous integrated boost [ 56 ]. In a recent systematic review and meta-analysis, particle therapy, including protons, led to a significantly higher 1-year OS rate when compared to CRT or SBRT [ 57 ].…”
Section: Clinical Datamentioning
confidence: 99%
“… 99 Hou et al 15 compared treatment outcomes based on the location of the tumor thrombus in patients with HCC and macrovascular invasion, reporting that patients with inferior vena cava tumor thrombi showed significantly better response rates to EBRT than those with portal vein tumor thrombi. Additionally, Wu et al 102 conducted a meta-analysis on the treatment outcomes in patients with HCC and macrovascular invasion, according to the RT modality. They reported that proton therapy showed significantly better 1-year and 2-year OS compared with conventional RT or SBRT (proton therapy vs. conventional RT, P =0.005 for 1-year OS, P =0.001 for 2-year OS; proton therapy vs. SBRT, P =0.002 for 1-year OS, P =0.004 for 2-year OS).…”
Section: Ebrt In Advanced Hcc With Macrovascular Invasionmentioning
confidence: 99%